2022
DOI: 10.3390/biomedicines10102620
|View full text |Cite
|
Sign up to set email alerts
|

From Cytokine Storm to Cytokine Breeze: Did Lessons Learned from Immunopathogenesis Improve Immunomodulatory Treatment of Moderate-to-Severe COVID-19?

Abstract: Complex immune response to infection has been highlighted, more than ever, during the COVID-19 pandemic. This review explores the immunomodulatory treatment of moderate-to-severe forms of this viral sepsis in the context of specific immunopathogenesis. Our objective is to analyze in detail the existing strategies for the use of immunomodulators in COVID-19. Immunomodulating therapy is very challenging; there are still underpowered or, in other ways, insufficient studies with inconclusive or conflicting results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 187 publications
0
12
0
Order By: Relevance
“…In majority of clinical cases, innate and adaptive immunity overcomes SARS-CoV-2 infection; however, some patients develop a severe late stage, which promotes the cytokine storm and accelerates the deterioration of patients to the ARDS/DAD ( Rondovic et al, 2022 ). The main pathological effect may be caused by hypersensitivity reactions rather than the virus itself, as Zhenfei et al reported that formaldehyde-inactivated SARS-CoV-2 induces ARDS in human ACE2-transgenic mice ( Bi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In majority of clinical cases, innate and adaptive immunity overcomes SARS-CoV-2 infection; however, some patients develop a severe late stage, which promotes the cytokine storm and accelerates the deterioration of patients to the ARDS/DAD ( Rondovic et al, 2022 ). The main pathological effect may be caused by hypersensitivity reactions rather than the virus itself, as Zhenfei et al reported that formaldehyde-inactivated SARS-CoV-2 induces ARDS in human ACE2-transgenic mice ( Bi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In majority of clinical cases innate and adaptive immunity overcomes SARS-CoV-2 infection, however, some patients develop a severe late stage, which promotes the cytokine storm and accelerates the deterioration of patients to the ARDS/DAD [56]. The main pathological effect may be caused by hypersensitivity reactions rather than virus itself, as study by Zhenfei et al reported that formaldehyde-inactivated SARS-CoV-2 induces ARDS in human ACE2-transgenic mice [57].…”
Section: Discussionmentioning
confidence: 99%
“…It is quite obvious that the scientific community has sufficiently emphasized the importance of T-cell-mediated adaptive immune responses for the clearance of the virus and long-term antiviral immunity. However, it is important to consider that T-cell exhaustion can significantly contribute to the exaggerated release of the cytokines, commonly known as a cytokine storm, in severely infected patients with COVID-19 [ 35 , 36 , 128 , 129 ]. T-cell exhaustion is a condition in which CD8+ T cells might develop metabolic malfunctions.…”
Section: T-cell Exhaustion and Disease Severitymentioning
confidence: 99%